Fractional filter IMC-PID controller design for second order plus time delay processes. Issue 1 (1st January 2017) - Ranganayakulu, R.; Uday Bhaskar Babu, G.; Seshagiri Rao, A.
Abstract: This article presents a simple method of designing a fractional filter PID controller for second order plus time delay (SOPTD) processes using internal model control (IMC) scheme. There has been limited number of tuning rules for SOPTD processes developed using direct synthesis method and IMC method. The proposed IMC-PID controller using fractional IMC filter results in a controller structure composed of PID controller cascaded with fractional filter. Simulations have been performed on several second order lag dominant and delay significant processes. Robustness checks are performed for variations in the process parameters and robustness analysis is carried out using sensitivity functions. The proposed controller results in an enhanced control performance for nominal process parameters and with parameter variations. In addition, the effect of measurement noise is also studied for set point tracking and load disturbance variations.